Cardiac magnetic resonance versus transthoracic echocardiography for the assessment and quantification of aortic regurgitation in patients undergoing transcatheter aortic valve implantation. Issue 24 (14th August 2014) - Ribeiro, Henrique B; Le Ven, Florent; Larose, Éric; Dahou, Abdellaziz; Nombela-Franco, Luis; Urena, Marina; Allende, Ricardo; Amat-Santos, Ignacio; Ricapito, Maria de la Paz; Thébault, Christophe; Clavel, Marie-Annick; Delarochelliére, Robert; et al.
Abstract : Background: The transthoracic echocardiographic (TTE) evaluation of the severity of residual aortic regurgitation (AR) following transcatheter aortic valve implantation (TAVI) has been controversial and lacks validation. Objectives: This study sought to compare TTE and cardiac magnetic resonance (CMR) for assessment of AR in patients undergoing TAVI with a balloon-expandable valve. Methods: TTE and CMR exams were performed pre-TAVI in 50 patients and were repeated postprocedure in 42 patients. All imaging data were analysed in centralised core laboratories. Results: The severity of native AR as determined by multiparametric TTE approach correlated well with the regurgitant volume and regurgitant fraction determined by CMR prior to TAVI (Rs =0.79 and 0.80, respectively; p<0.001 for both). However, after TAVI, the correlation between the prosthetic AR severity assessed by TTE and regurgitant volume and fraction measured by CMR was only modest (Rs =0.59 and 0.59, respectively; p<0.001 for both), with an underestimation of AR severity by TTE in 61.9% of patients (1 grade in 59.5%). The TTE jet diameter in parasternal view and the multiparametric approach (Rs =0.62 and 0.59, respectively; both with p<0.001) showed the best correlation with CMR regurgitant fraction post-TAVI. The circumferential extent of prosthetic paravalvular regurgitation showed a poor correlation with CMR regurgitant volume and fraction (Rs =0.32, p=0.084; Rs =0.36, p=0.054, respectively). Conclusions: The severity of AR following TAVI with a balloon-expandable valve was underestimated by echocardiography as compared with CMR. The jet diameter, but not the circumferential extent of the leaks, and the multiparametric echocardiography integrative approach best correlated with CMR findings. These results provide important insight into the evaluation of AR severity post-TAVI.